A new species of Colubrina (Rhamnaceae) of the Amazon region of Ecuador - Palacios, Walter (Phytotaxa, 2015)
A new species of Colubrina from the Amazon region of Ecuador is described and illustrated. The species is characterized by its elliptical and distichously arranged leaves, 10–18 × 4–8 cm, and the presence of basal, concave elliptical, glands, the short-shoots of the inflorescence with few nodes and seeds with two inner sides flat-concave and third side, as wide as the previous two and convex. The new species has been widely collected in areas below 700 m, and is expected to occur in similar habitats in the border areas of Colombia and Peru.